Peranan Auksin dalam Usaha Menekan Kelayuan Buah Muda Kakao (Theobroma Kakao L.) - Pangaribuan, Nurmala (LPPM Universitas Terbuka, 2004)
In the cocoa tree, the genes for producing an abscission zone are in pedicles. The process is hormonally driven by ethylene whilst auxins apparently decrease the sensitivity to ethylene. When the level of auxin declones, a special layer of cells (the abscission layer) is formed at the base of petiole or fruit stalk. Ethylene stimulates the production of enzimes that degrade the middle lamella beetween cells in the abscission zone. The concept development so far is correct that should be possible to delay abscission by aplication of sinthetic auxins. Aplication of compound enhance levels of auxins or decrease absicic acid and /or ethylene. Such conditions may inhibit young fruit abscission and promote fruit development.